Determinants and Outcomes of Mortality among Extremely Preterm Infants From a Tertiary Hospital in Thailand: 15-Year Experience - Waricha Janjindamai; Anucha Thatrimontrichai; Supaporn Disneevate; Gunlawadee Maneenil (Journal of Health Science and Medical Research (JHSMR), 2022)
Objective: It remains unclear if changes in neonatal care have resulted in better outcomes for extremely preterm infants (EPTs). This study was to evaluate neonatal mortality and morbidity in EPTs. Material and Methods: A retrospective cohort study of EPTs at a gestational age (GA) ≤28 weeks, who were admitted to the neonatal intensive care unit between January 2004 and December 2018. The study was divided into 2 periods, from 2004-2010 and 2011-2018. The likelihood ratio test in Multiple Cox regression models were used to determine adjusted hazard ratios (aHR) for differences in mortality among the two periods. Results: A total of 188 EPTs were enrolled. The overall median (interquartile range), GA and birth weight of the enrolled infants were 26 (25, 27) weeks and 780 (667, 875) g, respectively. The mortality rate was 66/188 (35.1%). The mortality rate between 2004-2010 and 2011-2018 decreased from 44.6% to 32.8%, but was not statistically significant (p-value=0.170). Multiple Cox regression analysis of mortality rate demonstrated statistical significance with infants of 23-24 and 25-26 weeks GA VS 27-28 weeks GA [aHR 3.85, 95% confidence interval (CI) (1.95, 7.58), p-value<0.010] and [aHR 1.92, 95% CI (1.09, 3.35), p-value<0.010], respectively. Pregnancy complications [aHR 2.24, 95% CI (0.96, 5.24), p-value=0.040)] and EPTs intubated VS early CPAP at birth [aHR 2.41, 95% CI (1.36, 4.25), p-value<0.010] were statistically significant. Conclusion: The mortality rate of EPTs decreased with advancing GA. Prenatal care of pregnancy complications and improving care practices might reduce the mortality rate.